Pseudo-Hadis Seputar Pendidikan Islam dan Sebarannya di Internet - Amrulloh, Amrulloh (RIWAYAH, 2018)
In the context of Islamic education or tarbawī Ḥadīth in the writings that exist on the internet, many expressions spoken by other than the Prophet are shown as the Ḥadīth of the Prophet, as many of the sayings are also propounded to the Prophet but have no origin. That is pseudo- Ḥadīth about Islamic education. Unfortunately, the reality is less even sometimes not realized at all by the public. This research is one of the forms and efforts so that pseudo- Ḥadīth can be realized and can’t be widespread more. Here the author intends to reveal the pseudo-Ḥadīth about Islamic education and it’s spread on the internet. To arrive at the intended purpose, here the author applies descriptive-analytical method using takhrīj approach. This study proves that a number of pseudo-hadiths about Islamic education are widespread in writings that exist on the internet.